PROFIL PENGEMBANGAN PROFESIONAL GURU - Sutrisno, Budi; Aisyah, Aisyah (Jurnal VARIDIKA, 2012)
This study is to describe the developent of pedagogical competence, professional competence, personal competence, and social competence of the International Standard Pioneer School in State Senior High School 1 Temanggung. The focus in this study were teacher professional development  of the international  standard pioneer school in State Senior High School 1 Temanggung, by observing the development of pedagogical competence, competence professional, personal competence, and social competence of the international   standard pioneer school in State Senior High School 1 Temanggung. The study is the qualitative research with the ethnography approach. This research was conducted in State Senior High School 1 Temanggung year 2010/2011, the source of the data  obtained  from  the  principal,  vice  principal,  head  of  the  International  Standard Pioneer School programs, teachers, librarians, and students. Data collected by in-depth interviews, observation, and documentation. Validity of the data was done by triangulation techniques. Analysis of the data used is a model of interactive analysis.   The results of this research can be concluded that the development of pedagogical competence of teachers  of the international   standard pioneer school in State Senior High School 1 Temanggung teachers include longer emphasizes the management aspects of learning, the development of  professional competence include the  aspect  of  improving the  skills  and  aspects of knowledge, competence development aspects of personality include mental, spiritual, and the  formation  of  professional  ethics  that  provides  a  change  in  attitude  teachers  in managing learning, while the component that was developed in the social competence includes the development of emotional intelligence, and development of teachers' roles in professional organizations (MGMP). Developed in the fourth aspect is the competence of the teacher professional development efforts that improve teacher quality, and improving the quality of the learning process that led to improved quality of learning outcomes in schools  RSMABI. Strategi  used  in  the  professional development of    the  international standard pioneer school in State Senior High School 1 Temanggung teachers is through training activities  conducted both  central  and  local  government, or  in-house training workshops held in schools, mentoring subject teachers by the facilitator / lecturer, teacher participation in professional organizations MGMP;   procurement S-2 scholarships for further studies in Mathematics and Science teachers. Constraints are found covering the internal factors are lack of motivation of teachers, school layout, and inadequate infrastructure, as well as external factors are lack of support from Temanggung District government in improving the educational qualifications (S-2).